2014
DOI: 10.3390/md12073929
|View full text |Cite
|
Sign up to set email alerts
|

Marine Microorganism-Invertebrate Assemblages: Perspectives to Solve the “Supply Problem” in the Initial Steps of Drug Discovery

Abstract: The chemical diversity associated with marine natural products (MNP) is unanimously acknowledged as the “blue gold” in the urgent quest for new drugs. Consequently, a significant increase in the discovery of MNP published in the literature has been observed in the past decades, particularly from marine invertebrates. However, it remains unclear whether target metabolites originate from the marine invertebrates themselves or from their microbial symbionts. This issue underlines critical challenges associated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
59
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(61 citation statements)
references
References 152 publications
(234 reference statements)
0
59
0
2
Order By: Relevance
“…The ANOSIM further confirmed that coral fragmentation did not significantly affect (R = 0.302; P = 0.086) the structure of the bacterial community recorded in the mother colonies and coral fragments stocked under the same PAR intensity (120 μmol quanta m −2 s −1 ). These results are relevant to support in toto aquaculture (the culture of the holobiont-cnidarian host and associated microorganisms) as a tool to supply microbial biomass associated with marine invertebrates, namely corals, for drug discovery (Leal et al, 2013(Leal et al, , 2014. Indeed, if no significant shifts occur in the structure of the bacterial community present in coral fragments, in toto aquaculture may contribute to solve the "supply problem" (see Leal et al, 2014), as microorganisms producing target metabolites in mother colonies are more likely to have been retained during fragmentation and/or growout.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…The ANOSIM further confirmed that coral fragmentation did not significantly affect (R = 0.302; P = 0.086) the structure of the bacterial community recorded in the mother colonies and coral fragments stocked under the same PAR intensity (120 μmol quanta m −2 s −1 ). These results are relevant to support in toto aquaculture (the culture of the holobiont-cnidarian host and associated microorganisms) as a tool to supply microbial biomass associated with marine invertebrates, namely corals, for drug discovery (Leal et al, 2013(Leal et al, , 2014. Indeed, if no significant shifts occur in the structure of the bacterial community present in coral fragments, in toto aquaculture may contribute to solve the "supply problem" (see Leal et al, 2014), as microorganisms producing target metabolites in mother colonies are more likely to have been retained during fragmentation and/or growout.…”
Section: Resultsmentioning
confidence: 97%
“…These results are relevant to support in toto aquaculture (the culture of the holobiont-cnidarian host and associated microorganisms) as a tool to supply microbial biomass associated with marine invertebrates, namely corals, for drug discovery (Leal et al, 2013(Leal et al, , 2014. Indeed, if no significant shifts occur in the structure of the bacterial community present in coral fragments, in toto aquaculture may contribute to solve the "supply problem" (see Leal et al, 2014), as microorganisms producing target metabolites in mother colonies are more likely to have been retained during fragmentation and/or growout. Well established protocols for the propagation ex situ of Sarcophyton are already available (Calfo, 2007;Sella and Benayahu, 2010), which allow the production of coral biomass using simple and economically feasible zootechnical procedures.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…In fact it is estimated that as many as 99% are considered "unculturable" [107], thus making the screening and mass-production of any pharmaceuticals they produce very difficult using common culturing methods [85]. One seemingly simple solution to this problem is to culture the host organism along with the symbiont, in a manner that maximises secondary metabolite production by the microbe [21, 108,109]. However, this adds an extra level of complexity to the culturing procedure, having to accommodate the needs of an entire complex holobiont.…”
Section: Constraints and Future Prospectsmentioning
confidence: 99%
“…For instance, marine sponges are valued for their ecosystem services, in particular cycling and retaining nutrients on coral reefs (Alexander et al, 2014;de Goeij et al, 2013;Rix et al, 2016), and as a source of bioactive secondary metabolites with commercial potential (Blunt et al, 2014;Konstantinidis & Tiedje, 2004;Leal et al, 2012;Mehbub et al, 2014;Thomas et al, 2010). It is accepted that the low commercialisation rate of sponge holobiont derived natural products is due to the inability to reliably produce sponge biomass (Belarbi, 2003;Leal et al, 2014;Osinga et al, 1999;Schippers et al, 2012;Sipkema et al, 2005;Wijffels, 2008). Simplified, growth is the catabolic and anabolic conversion of food by the central metabolic network into biomass.…”
Section: Overviewmentioning
confidence: 99%